Efektivitas Pelaksanaan Pelayanan Pengaduan Masyarakat Berbasis E-Government - Mahendra, Gerry Katon; Pribadi, Ulung (Universitas Muhammadiyah Yogyakarta, 2014)
Public complaints service todayâs has become part ofÂ the efforts to improve public services in Indonesia. Government,both central and local levels is appropriate to give special attention to the improvement ofÂ service quality ofÂ publiccomplaints. The governmentâs attention can be achieved either by continuously innovate to create public complaintsservice that is not only easily accessible by the public, butÂ also can be received and respondedÂ to effectively by localgovernment. Yogyakarta Cityâs Government innovates by providing the services ofÂ public complaints were based oninformation technology and communication (e-government). Innovations made by the government ofÂ Yogyakar ta isexpected to provide ease ofÂ access for the public and can be input which should be followed up effectively by thegovernment ofÂ the city ofÂ Yogyakarta so as to create improved quality ofÂ public services in general in the future.